Facing Digital Age: Should the Regional Regulation Be Made Digitally? - Fatkhurohman, Fatkhurohman; Sirajuddin, Sirajuddin; Al Fatih, Sholahudin (Universitas Negeri Gorontalo, 2025)
In forming a Regional Regulation, the Regent must interact formally with the Governor and the Ministry of Law and Human Rights through a facilitation and consultation evaluation mechanism. Providing recommendations for assessing draft regional regulations can confuse those proposing them because suggestions for improvements between the Governor and the Ministry of Law and Human Rights are not well coordinated and are carried out manually. This research aims to find a solution by optimizing coordination methods with digital application networks, especially in establishing regional regulations so that they occur quickly and accurately. This research will later be carried out using an empirical juridical approach, where researchers will delve more into primary data by discovering countless realities in the field regarding the effectiveness and efficiency of the implementation of evaluations by the Governor and the Ministry of Law and Human Rights during the implementation of the assessment of draft regional regulations. This research shows that coordination between the Governor and the Ministry of Law and Human Rights needs to be carried out jointly based on an agreement in evaluating regional regulation proposals so that assessments are distinct. To make this process runeffectively and efficiently, it is better to do it online via a digital application.